Hydrothermal synthesis of a crystalline rutile TiO2 nanorod based network for efficient dye-sensitized solar cells - Yu, H.; Pan, Jian; Bai, Y.; Zong, X.; Li, X.; Wang, L. (2013)
One-dimensional (1D) TiO2 nanostructures are desirable as photoanodes in dye-sensitized solar cells (DSSCs) due to their superior electron-transport capability. However, making use of the DSSC performance of 1D rutile TiO2 photoanodes remains challenging, mainly due to the small surface area and consequently low dye loading. Herein, a new type of photoanode with a three-dimensional (3D) rutile-nanorod-based network structure directly grown on fluorine-doped tin oxide (FTO) substrates was developed by using a facile two-step hydrothermal process. The resultant photoanode possesses oriented rutile nanorod arrays for fast electron transport as the bottom layer and radially packed rutile head-caps with an improved large surface area for efficient dye adsorption. The diffuse reflectance spectra showed that with the radially packed top layer, the light-harvesting efficiency was increased due to an enhanced light-scattering effect. A combination of electrochemical impedance spectroscopy (EIS), dark current, and open-circuit voltage decay (OCVD) analyses confirmed that the electron-recombiantion rate was reduced on formation of the nanorod-based 3D network for fast electron transport. As a resut, a light-to-electricity conversion efficiency of 6.31 % was achieved with this photoanode in DSSCs, which is comparable to the best DSSC efficiencies that have been reported to date for 1D rutile TiO2. Rooting for rut Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.